Correlation between strength related parameters and ski-jumping performance in junior ski-jumpers - Fritz, J.; Lindinger, S. J.; Schwameder, H. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Ski-jumping is a very complex sport. Especially the take-off poses a high challenge to the athletes. The aim of the take-off is to reach high vertical release velocity in combination with a sufficient large forward rotating angular momentum (Schwameder, 2008). Strength training of the lower limbs and imitation jumps are used to enhance the take-off performance in dry land situations. It is not known, however, if the dry land performance correlates with the actual ski-jumping performance in general and in junior ski-jumpers in particular. Thus, the aim of this study was to investigate the correlations between parameters from isometric strength tests and jump tests with the ski-jumping performance in junior ski-jumpers.